Evolution of LPSO phases in a Mg-Zn-Y-Gd-Zr alloy during semi-continuous casting, homogenization and hot extrusion. (15th August 2018) - Chen, Tao; Chen, Zhiyong; Shao, Jianbo; Wang, Renke; Mao, Longhui; Liu, Chuming
Abstract: A large size Mg-1.2Zn-3.4Y-4.7Gd-0.5Zr (wt%) alloy sheet was manufactured by semi-continuous casting, homogenization and hot extrusion, in which the microstructures were systematically examined. The results showed that: (i) During homogenization, the generation of 14H LPSO phase was mainly achieved by two phase transition processes of "Mg5 (Gd, Y, Zn) phase → 14H LPSO phase" and "18R LPSO phase → 14H LPSO phase". (ii) During extrusion, the evolution of LPSO phases with various morphologies was driven by severe deformation and dynamic recrystallization (DRX). Under severe deformation, the 14H LPSO phases in homogenized alloy were broken down to fragments with various sizes. Under the influence of DRX, the deformation defects of small LPSO fragments were fully eliminated and formed the "sandwich-like" LPSO phase. While the deformation defects of coarse LPSO fragments were less eliminated and formed the "irregular-shaped" LPSO phase. Meanwhile, due to the decreased solubility of Zn, Y and Gd in the extruded alloy matrix, the solution elements of Zn, Y and Gd were impelled to precipitate at the scattering arranged stacking faults (SFs) and formed the "needle-like" LPSO phase. It is found that the gliding of Shockley partial dislocation(s) on basal plane was structurally needed during the precipitation of needle-like LPSO phase. Graphical abstract: Unlabelled Image Highlights: Mg5 (Gd, Y, Zn) → 14H LPSO and 18R LPSO → 14H LPSO co-exist during homogenization. Severe deformation and DRX promote the evolution of LPSO phases during extrusion. Zn, Y and Gd precipitate at stacking faults and form the needle-like LPSO phase. Gliding of Shockley partial dislocations on basal plane is structural needed during precipitation of LPSO.